2015
DOI: 10.1021/ja508597d
|View full text |Cite
|
Sign up to set email alerts
|

Light Activation of Protein Splicing with a Photocaged Fast Intein

Abstract: Intein-mediated protein splicing has found broad biotechnological applications. Herein, we describe our recent result in engineering a photoactivatable intein compatible with living mammalian cells. A photocaged cysteine amino acid residue was genetically introduced into a highly efficient Nostoc punctiforme (Npu) DnaE intein. The resulting photocaged intein was inserted into a red fluorescent protein (RFP) mCherry and a human Src tyrosine kinase to create inactive chimeric proteins. A light-induced photochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 38 publications
0
54
0
Order By: Relevance
“…Numerous applications of optical control of protein function using UAA mutagenesis have been demonstrated, including control of protein localization, [65] DNA transcription, [66] DNA recombination, [67] intein splicing, [68] protease activity, [69] epigenetic events, [70] and protein phosphorylation. [71] …”
Section: Optical Control Of Proteins and Peptidesmentioning
confidence: 99%
“…Numerous applications of optical control of protein function using UAA mutagenesis have been demonstrated, including control of protein localization, [65] DNA transcription, [66] DNA recombination, [67] intein splicing, [68] protease activity, [69] epigenetic events, [70] and protein phosphorylation. [71] …”
Section: Optical Control Of Proteins and Peptidesmentioning
confidence: 99%
“…This has been used in numerous studies to control protein function in living cells [53]. Examples from recent literature are the creation of light-activatable CRISPR/Cas9 [54], TEV protease [55] and inteins [56]. Photoactivation of an oncogenic mutant of isocitrate dehydrogenase 2 revealed immediate changes in metabolism and DNA 5-hydroxymethylcytosin levels, demonstrating how a genetic mutation causes perturbations in epigenetic states [57].…”
Section: Photo-activation Of Protein Activitymentioning
confidence: 99%
“…Toward this goal, unnatural amino acids masked with light‐removable protecting groups can be site‐specifically introduced at key residues in target proteins through genetic code expansion in pro‐ and eukaryotic cells. This methodology enables the optical regulation of a wide range of biological processes, including DNA unwinding, DNA recombination, transcription, protein folding, protein localization, protein phosphorylation, protein splicing, protein cleavage, ion channel activity, and other enzymatic processes . Recently, it was demonstrated that the caged tyrosine NBY can be genetically encoded in mammalian cells expressing an engineered pyrrolysyl‐tRNA synthetase (PylRS)/tRNA CUA pair, despite the fundamentally different architecture of NBY and pyrrolysine .…”
Section: Introductionmentioning
confidence: 99%